2023
DOI: 10.1039/d3ra01438j
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide supported ionic liquid/Fe complex: a robust and highly stable nanocatalyst

Abstract: A novel nano-graphene oxide supported ionic liquid/Fe (NGO/IL–Fe) is prepared, characterized and used as a powerful and highly recoverable nanocatalyst in the synthesis of tetrahydrobenzo[b]pyrans under green conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These compounds have a high ability to stabilize polar and charged catalysts due to their inherent ionic nature. For instance, imidazolium-based ionic liquids are highly effective in stabilizing transition metal complexes, thereby enhancing their catalytic activities ( Ni and Headley, 2010 ; Karimi et al, 2018 ; Gao et al, 2021 ; Taheri et al, 2023 ). Thus, combining imidazolium-based ILs with polyethylene supports provides remarkable properties, including high activity, selectivity, and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have a high ability to stabilize polar and charged catalysts due to their inherent ionic nature. For instance, imidazolium-based ionic liquids are highly effective in stabilizing transition metal complexes, thereby enhancing their catalytic activities ( Ni and Headley, 2010 ; Karimi et al, 2018 ; Gao et al, 2021 ; Taheri et al, 2023 ). Thus, combining imidazolium-based ILs with polyethylene supports provides remarkable properties, including high activity, selectivity, and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…These properties make GO an attractive candidate for a catalytic substrate in synthesizing organic materials, especially via MCRs. [35][36][37][38][39][40][41] MCRs are synthetic processes that produce products from several reactants simultaneously in one-pot reactions. Recently, a wide range of MCRs have been developed using various catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have many biological properties, including antioxidant, antitumor or anticancer, antianaphylactic, antispasmodic, and antiinflammatory. 36,[60][61][62][63] Also, recent studies have shown these heterocycles can be effective in the treatment of some diseases such as Alzheimer's, Down's syndrome, Schizophrenia, Parkinson's, etc. 49,64,65 Different protocols have been introduced for the synthesis of tetraketone and tetrahydrobenzo[b]pyran derivatives by using a variety of catalysts in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations